2017
DOI: 10.1186/s12645-017-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

An overview of current practice in external beam radiation oncology with consideration to potential benefits and challenges for nanotechnology

Abstract: Over the past two decades, there has been a significant evolution in the technologies and techniques employed within the radiation oncology environment. Over the same period, extensive research into the use of nanotechnology in medicine has highlighted a range of potential benefits to its incorporation into clinical radiation oncology. This short communication describes key tools and techniques that have recently been introduced into specific stages of a patient’s radiotherapy pathway, including diagnosis, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…The nanomaterials present wide potential for medical use, including tissue engineering protein detection and drug and/or gene delivery. The inclusion of nanoparticles (NPs) into both diagnostic and radiation therapy settings, emphasizing their use as potential agents in the combination of diagnosis and therapeutics, may be promising 81 , 82 .…”
Section: Introductionmentioning
confidence: 99%
“…The nanomaterials present wide potential for medical use, including tissue engineering protein detection and drug and/or gene delivery. The inclusion of nanoparticles (NPs) into both diagnostic and radiation therapy settings, emphasizing their use as potential agents in the combination of diagnosis and therapeutics, may be promising 81 , 82 .…”
Section: Introductionmentioning
confidence: 99%
“…Iodine-based contrast agents have been widely applied in clinical diagnosis, including extracellular fluid, vascular space, hepatocellular, and tissue-specific imaging [150,151]. Moreover, a number of research groups have recently reported the use of high atomic number NPs, such as Au [152,153], Gd [154,155], Hf [156], and Bi [157,158] in oncology to assess and track changes in tumor neo-vasculature and has enabled clinicians to evaluate tumor response to therapeutic agents [159,160]. Amongst the emerging NP-based contrast agents, AuNP, which exhibits high x-ray attenuation, biocompatibility, facile synthesis, and surface functionalization, has been introduced into commercial products, e.g., Aurimmune and Auroshell [161].…”
Section: Going Deepermentioning
confidence: 99%
“…Radioisotope imaging is an emerging technology over CT and MRI provide better diagnosis value in oncology eg: fluorodeoxyglucose is radioactive using in research. Radio-sensitizing NPs have effective tumor control in oncology therapy combines X-ray with a high atomic number shows strong photoelectric absorption of x-ray which increases distribution of malignant cell [19]. Radiosensitive nano-particles extensively used in cancer research.…”
Section: Radiotherapymentioning
confidence: 99%
“…Radiosensitive nano-particles extensively used in cancer research. Modulated Radiation Therapy and volumetric modulated ARC Therapy, IGRI radiotherapy with a combined effect of NPs are in development adopting new avenues of research [19]. Versatility of nano-particles provide potential to probe critical cancer targets and identify imaging biomarkers in clinical trials, eg: targeted particle radiotherapies and use of radio-sensitizing nano-material with high atomic number Z enhance the efficiency of radiation to tumor [13].…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation